Gerakan Masyarakat Cerdas Menggunakan Obat Dengan Edukasi “Tanya Lima O” - Krisnawati, Monik (LPPM STIKES Madani, 2023)
The availability of several pharmacies in Sendangsari Village influences the increase in community self-medication behavior. Based on Pharmacy Service Standards, pharmacists are obliged to provide drug information services to patients. GeMa CerMat, or